Constructing Low‐Impedance Li7La3Zr2O12‐Based Composite Cathode Interface for All‐Solid‐State Lithium Batteries. Issue 12 (9th October 2022) - Zhao, Le; Zeng, Yaping; Fu, Liang; Zhang, Jiaming; Sun, Dan; Tang, Yougen; Ren, Yu; Pan, Fusheng; Wang, Haiyan
Abstract : Garnet‐type solid‐state electrolytes (SEs) represented by Li7 La3 Zr2 O12 (LLZO) are considered ideal ion‐conducting materials for oxide all‐solid‐state lithium batteries (ASSLBs) due to their high ionic conductivity and wide electrochemical window. However, there are still many problems at the interface of the composite cathode side with LLZO‐based SEs as ion conductors as LLZO has poor interfacial contact with other particles and shows air instability when exposed to air because of the spontaneous reaction with water and CO2 . Among them, the high impedance at the interface is a key issue that severely limits the actual energy density and cycle life of ASSLBs. With the optimized modification of LLZO‐based SEs and the in‐depth study of the interfacial mechanism, some breakthroughs have been made in the electrochemical performance of LLZO‐based ASSLBs. Hence, this review first describes the factors causing high interfacial impedance inside LLZO‐based composite cathode, such as poor interparticle contact, stress disruption and elemental diffusion at the interface, and discontinuous ion/electron percolation paths and then summarizes the solution strategies, for example, microstructure design, component optimization, and internal interface modification. Finally, the development prospect of LLZO‐based ASSLBs composite cathode is prospected to provide a useful reference for exploring the practical application of LLZO‐based ASSLBs. Abstract : Herein, a comprehensive summary of the internal interface issues of Li7 La3 Zr2 O12 ‐based(LLZO‐based) composite cathodes for all‐solid‐state batteries is presented, detailing the internal Li + transport mechanism, the source of high interfacial impedance, and the optimization strategies for LLZO‐based composite cathode. In addition, the prospective developments of LLZO‐based composite cathodes are presented with aspirations to provide useful guidance for their practical applications.